Peran Prediktif IL-6, IL-10, dan TNF-α Plasma terhadap Gagal Ginjal Akut pada Pasien dengan COVID-19 Derajat Sedang dan Berat - Gathmyr, Dewi; Bonar, Maruhum Bonar H; Susilo, Adityo; Harimurti, Kuntjoro; Nainggolan, Ginova; Tagor, Alvin; Shatri, Hamzah; Lesmana, Cosmas Rinaldi Adithya; Amin, Zulkifli (UI Scholars Hub, 2025)
Introduction. Acute kidney injury (AKI) is associated with higher mortality rate in COVID-19 patients due to inflammation and immune dysregulation. This study aimed to correlate serum levels of IL-6, IL-10, and TNF-α with serum creatinine changes and their roles to predict incidence of acute kidney injury (AKI) in patients with moderate and severe COVID-19. Methods. This prospective cohort study was conducted among patients with moderate to severe COVID-19 in Pertamina Central Hospital Jakarta, Indonesia during November 2020 to January 2021. All serum levels of cytokines (IL-6, IL-10, and TNF-α) and creatinine were collected on the first day and seventh day of hospitalization. They might be collected earlier if the patients died or discharged early. AKI was defined as deterioration in serum creatinine or urine output based on Kidney Disease Improving Global Outcomes (KDIGO) guideline. The correlation between cytokine and creatinine serum level changes were analyzed using Spearman test. Receiver operator characteristic curve was calculated to explore predictive roles of cytokines on AKI incidence. Results. A total of 43 patients were included in the study, with a mean age of 59.3 years (SD 12.59), and the majority were male (74%). The incidence of AKI was 7%. Serum creatinine changes were correlated with serum levels changes IL-10 (r= -0.343; p=0.024), but not for IL-6 (r=-0.198; p=0.202) and TNF-α (r=-0.129, p=0.409). Meanwhile, serum TNF-α level on the first day was able to predict AKI incidence on the seventh day of hospitalization (AUC 85%; p=0.045; 95% CI=0.737 to 0.963). Conclusions. TNF-α on the first day is potential to be predictor on AKI incidence on the seventh day in moderate and severe COVID-19 patients.